En route towards the peptide γ‐helix: X‐ray diffraction analyses and conformational energy calculations of Adm‐rich short peptides. (22nd December 2016) - Mazzier, Daniela; Grassi, Luigi; Moretto, Alessandro; Alemán, Carlos; Formaggio, Fernando; Toniolo, Claudio; Crisma, Marco
Abstract : We performed the solution‐phase synthesis of a set of model peptides, including homo‐oligomers, based on the 2‐aminoadamantane‐2‐carboxylic acid (Adm) residue, an extremely bulky, highly lipophilic, tricyclic, achiral, C α ‐tetrasubstituted α ‐amino acid. In particular, for the difficult peptide coupling reaction between two Adm residues, we took advantage of the Meldal's α ‐azidoacyl chloride approach. Most of the synthesized Adm peptides were characterized by single‐crystal X‐ray diffraction analyses. The results indicate a significant propensity for the Adm residue to adopt γ ‐turn and γ ‐turn‐like conformations. Interestingly, we found that a ‐CO‐(Adm)2 ‐NH‐ sequence is folded in the crystal state into a regular, incipient γ ‐helix, at variance with the behavior of all of the homo‐dipeptides from C α ‐tetrasubstituted α ‐amino acids already investigated, which tend to adopt either the β ‐turn or the fully extended conformation. Our density functional theory conformational energy calculations on the terminally blocked homo‐peptides ( n  = 2–8) fully confirmed the crystal‐state data, strongly supporting the view that this rigid C α ‐tetrasubstituted α ‐amino acid residue is largely the most effective building block for γ ‐helix induction, although to a limited length (anti‐cooperative effect). Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : 2‐Aminoadamantane‐2‐carboxylic acid (Adm) was proven to enjoy a significant propensity to adopt γ‐turn and γ‐turn‐like conformations. The onset of a regular, incipent γ‐helix (two consecutive γ‐turns) was crystallographically documented for a ‐CO‐(Adm)2 ‐NH‐ sequence.